Effectiveness of tyre chips as alternative material in inclined gabion wall to mitigate slope failure - Muhamad Wafiy, Idzani (2018)
Slope failure is a common problem in tropical countries such as Malaysia, which is characterised by tropical region, weathering profile and a humid. The main factor of slope failure is cause by heavy rain because normally slides often occur after intense rainfall. A retaining wall is a structure that can retained soil behind it from sliding or eroded away. The most convenient type of retaining wall is gabion wall. A gabion wall is walls made of stacked wire meshes tied together and filled with gravel. However, the use of gravel in gabion needs to be decrease because the gravel quarrying is harmful to the environment .Thus; the solution to decrease usage of gravel in gabion wall is by combine the gravel with other material. Used tyres were chosen to combine with gravel that will fill up the gabion wall with certain percentage ratio. In this study by using slope model and simulation several of ratios that filled up in to gabion wall are tested against the sand slope with 60° angle that subjected artificial rainfall with intensity 570mm/h. From the result of the study, 50% Gravel mixed with 50% tyre chip as material for gabion wall is strength enough to prevent slope failure and provide support for vertical or near-vertical grade for small-scale model because the different between current practices by using 100% gravel is only 6%